Validity and reliability of the Thai version of the Utrecht Gender Dysphoria Scale-Gender Spectrum (UGDS-GS) in Thai youths and young adults with gender dysphoria - Jamneankal T. (2023)
Background Many people who are gender variant have undiagnosed gender dysphoria, resulting in delayed receipt of gender-affirming support and prolonged distress in living with their gender-non-conforming sex. The Utrecht Gender Dysphoria Scale-Gender Spectrum (UGDS-GS) is a newly developed tool that measures dissatisfaction with gender identity and expression. However, there is no translated version of this tool in Thai. Moreover, the sensitivity, specificity and cut-off point of the UGDS-GS to detect gender dysphoria in people who are transgender remain unknown. Aims This study translated the UGDS-GS into Thai and then examined the validity and reliability of the Thai UGDS-GS. Methods 185 participants with and without gender dysphoria were selected from the Gender Variation Clinic in Ramathibodi Hospital and from social media platforms. The UGDS-GS was translated into Thai according to the World Health Organization (WHO) guidelines on translation. The medical records of patients with gender dysphoria and semi-structured interviews were used to confirm the diagnosis of gender dysphoria. Subsequently, the validity and reliability of the instrument were analysed. Results The mean age of participants was 30.43 (7.98) years among the 51 assigned males (27.6%) and 134 assigned females (72.4%) at birth. The Thai UGDS-GS average score was 77.82 (9.71) for those with gender dysphoria (n=95) and 46.03 (10.71) for those without gender dysphoria (n=90). Cronbach's alpha coefficient was 0.962, showing excellent internal consistency. In addition, exploratory factor analysis showed compatibility with the original version's metrics. The value of the area under the curve was 0.976 (95% confidence interval: 0.954 to 0.998), indicating outstanding concordance. At the cut-off point of '60', sensitivity and specificity were good (96.84% and 91.11%, respectively). Conclusions The Thai UGDS-GS is an excellent, psychometrically reliable and valid tool for screening gender dysphoria in clinical and community settings in Thailand. The cut-off point of â € 60' scores suggests a positive indicator or a high chance of gender dysphoria.